Effects of recombinant LH supplementation to recombinant FSH during induced ovarian stimulation in the GnRH-agonist protocol: a matched case-control study - Franco, Jose G. [UNESP]; Baruffi, Ricardo L. R.; Oliveira, Joao Batista A. [UNESP]; Mauri, Ana L.; Petersen, Claudia G. [UNESP]; Contart, Paula; Felipe, Valeria (Biomed Central Ltd., 2009)
Background: Some studies have suggested that the suppression of endogenous LH secretion does not seem to affect the majority of patients who are undergoing assisted reproduction and stimulation with recombinant FSH (r-FSH). Other studies have indicated that a group of normogonadotrophic women down-regulated and stimulated with pure FSH preparations may experience low LH concentrations that compromise the IVF parameters. The present study aimed to compare the efficacy of recombinant LH (r-LH) supplementation for controlled ovarian stimulation in r-FSH and GnRH-agonist (GnRH-a) protocol in ICSI cycles.Methods: A total of 244 patients without ovulatory dysfunction, aged < 40 years and at the first ICSI cycle were divided into two groups matched by age according to an ovarian stimulation scheme: Group I (n = 122): Down-regulation with GnRH-a + r-FSH and Group II (n = 122): Downregulation with GnRH-a + r-FSH and r-LH (beginning simultaneously).Result(s): The number of oocytes collected, the number of oocytes in metaphase II and fertilization rate were significantly lower in the Group I than in Group II (P = 0.036, P = 0.0014 and P = 0.017, respectively). In addition, the mean number of embryos produced per cycle and the mean number of frozen embryos per cycle were statistically lower (P = 0.0092 and P = 0.0008, respectively) in Group I than in Group II. Finally the cumulative implantation rate (fresh+thaw ed embryos) was significantly lower (P = 0.04) in Group I than in Group II. The other clinical and laboratory results analyzed did not show difference between groups.Conclusion: These data support r-LH supplementation in ovarian stimulation protocols with r-FSH and GnRH-a for assisted reproduction treatment.